Analytical investigation of railway overhead contact wire dynamics and comparison with experimental results. (1st February 2019) - Anastasio, D.; Fasana, A.; Garibaldi, L.; Marchesiello, S.
Highlights: Continuous vibrating system analysis with non-proportional damping and axial load. System identification using subspace identification technique. Comparison between analytical predictions vs experimental outcomes and model updating. Abstract: In this paper an analytical method for studying the free response of continuous vibrating systems with distributed and possibly non-proportional viscous damping is proposed. The most general case the method refers to is a piece-wise homogeneous Euler-Bernoulli beam, with lumped elastic and inertial elements and subjected to tensile load. The practical application of the method to a contact wire is also presented, aiming at analysing its dynamic response. Contact wires are typically used in the overhead contact line of the railway electrification system but, despite their wide diffusion, their damping properties have not been exhaustively studied. This study aims at experimentally validate the analytical method to define a reliable dynamic model of overhead contact lines. The wire is modelled as an axially loaded homogeneous beam, with lumped elastic and inertial elements (i.e. droppers and clamps). A state-form expansion applied in conjunction with a transfer matrix technique is adopted to extract the eigenvalues and to express the eigenfunctions in analytical form. Experimental measurements have been carried out in the Dynamics & Identification Research Group (DIRG) laboratory of Politecnico di Torino considering two different damping scenarios, and the modal properties of the test bench have been extracted by using a linear subspace identification technique. The damping distribution is finally investigated starting from the experimental data, in order to seek for the most appropriate damping model.